Model dan Proses Komunikasi - Efendi, Erwan; Ramadhan, Nanda; Sari, Maya; Asya, Shadrina; Alhadi, Fahmi (VISA: Journal of Vision and Ideas, 2023)
Psychological and mechanistic paradigms are two different approaches to understanding and explaining human phenomena and the world around them. The psychology paradigm involves the study of human thoughts, behavior, and mental processes. This approach focuses on understanding how individuals think, feel, and act. Psychological paradigms include various theories and methods used to study human psychological aspects. On the other hand, the mechanistic paradigm involves the view that the world can be explained and understood through the principles of mechanics and causality. These two paradigms have differences in the way they view and explain human phenomena and the world. The psychological paradigm focuses more on the psychological and mental aspects of humans, while the mechanistic paradigm focuses more on the physical and mechanical aspects